Raw milk delivery at India's Mulukanoor Women's Cooperative Dairy - International Livestock Research Institute (International Livestock Research Institute, 2020)
How fresh raw milk is delivered, collected, tested and processed at the Mulukanoor Women's Cooperative Dairy in Telangana, India. Read more in the ILRI 2019 Annual Report: https://www.ilri.org/news/annual-report